RANCANG BANGUN SISTEM MANAJEMEN LAPAK PASAR BERBASIS WEB MOBILE - Arif Syam; Ahmad Maulid Asmiddin; Ahmad Ahmad (Prodi Teknik Informatika Unidayan Baubau, 2022)
Wameo Market is one of the traditional markets in Baubau City which plays an important role in promoting economic growth in the Buton Islands region. The existence of the Wameo market is very helpful, not only for the local government but also for the people who depend on trading activities. The management of the tax levy for the use of stalls is often delayed in reporting to the Trade and Industry Office of Baubau City due to the unavailability of a system that manages users of the Wameo market stalls. Therefore we need a system that can overcome these problems. This study aims to create a payment management system for market stall retribution payments electronically. The system development method used in this study is the Waterfall method. This research resulted in a user management application for the Wameo market shanties and the payment of lapak fees. Merchants can make payments with the application provided, so that field officers can easily make reports.